Leaf anatomy of Xylopia L. (Annonaceae), occurring in Ecological Park of Gunma, Santa Bárbara, Pará State - de Almeida, Eliane Francisca; Potiguara, Raimunda Conceição de Vilhena; Macedo, Eunice Gonçalves; Almeida Lins, Alba Lúcia Ferreira de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
Annonaceae shows several species which are producers of essential oil, among them Xylopia genus, that shows medicinal, pharmacological and biological properties. Thereby the present study has the purpose of knowing leaf anatomy, identify and locate secretory structures, besides to realize histochemical tests in Xylopia benthamii R.E. Fries and X. nitida Dunal species. Slides of epidermal dissociation were prepared to carry out this study, maceration, histological cuts and histochemical tests, according to usual protocols in plant anatomy, using optical light microscopy and electronic scanning. The results showed that both species differed in epidermal cell walls shape on adaxial surface, they present papillose abaxial surface, margin ending in vascular bundles, the stomata is located under epidermal cell level, striate cuticle and marginal vein presence. Before the results, the leaf anatomy of taxa studied helped to segregate them and made it possible to locate the secretory structures on both studied species.